Juridical Review Of The Criminal Act Of Online Fraud Is Reviewed From Law Number 19 Of 2016 Concerning Information And Electronic Transactions - Suci Ramadani (Yayasan Multidimensi Kreatif, 2023)
The crime of fraud is currently increasingly developing following the times and advances in technology, the Internet can also be used as a forum that can generate income opportunities to meet life's needs, namely by carrying out online business activities. This research discusses the legal regulations for criminal acts of fraud. online, what are the factors that cause online criminal acts of fraud, how to resolve online criminal acts Research Studies at the Binjai Police. This research was carried out using an empirical juridical method with a field research method, in which case the research method used was that the researcher went directly into the field to conduct interviews with sources and collected secondary data consisting of primary legal material and secondary legal material. The criminal act of online-based fraud is based on evidence or means of action, namely using an electronic system (computer, internet, telecommunications equipment). Law enforcement regarding this criminal act of fraud can still be accommodated by the Criminal Code and Law Number 11 of 2008 concerning Information and Electronic Transactions. Barriers to law enforcement against criminal acts of fraud based on electronic transactions are still influenced by five factors, namely legal factors, law enforcement factors, means or facilities that support law enforcement, community factors and cultural factors. Legal rules governing criminal acts of fraud in the Criminal Code and protection of consumers, factors for criminal acts of online fraud which include economic, environmental, social and cultural, intellectual and security factors.